Ex post evaluation of integrated soil fertility Management - CGIAR Research Program on Maize (2019)
data collected from Northern Ghana and Western Kenya and showed that the technology adoption leads to grain yield increase by up to 27% Northern Ghana and 16% in Western Kenya.